1999
DOI: 10.1007/s002329900597
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of K-Cl Cotransport in Frog Erythrocyte Membrane: Effect of External Sodium

Abstract: In frog red blood cells, K-Cl cotransport (i.e., the difference between ouabain-resistant K fluxes in Cl and NO(3)) has been shown to mediate a large fraction of the total K(+) transport. In the present study, Cl(-)-dependent and Cl(-)-independent K(+) fluxes via frog erythrocyte membranes were investigated as a function of external and internal K(+) ([K(+)](e) and [K(+)](i)) concentration. The dependence of ouabain-resistant Cl(-)-dependent K(+) ((86)Rb) influx on [K(+)](e) over the range 0-20 mm fitted the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Further studies eventually showed that the K + -Cl − cotransport mechanism was inhibited by the loop diuretic furosemide and the alkanoic acid DIOA [11, 23, 24]. They also shed light on the mechanisms by which this transport moiety is regulated in response to cell swelling.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies eventually showed that the K + -Cl − cotransport mechanism was inhibited by the loop diuretic furosemide and the alkanoic acid DIOA [11, 23, 24]. They also shed light on the mechanisms by which this transport moiety is regulated in response to cell swelling.…”
Section: Main Textmentioning
confidence: 99%
“…As for the effect of various agents on KCC1 activity per se, it was found to be as described in native cells types or tissues and similar among the isoforms. In essence, the pharmacological signature of KCC1 was characterized by the following traits: stimulation by N -ethylmaleimide, modest inhibition by bumetanide, DIDS, and barium, and stronger inhibition by furosemide and DIOA [11, 23, 24, 42, 43]. Importantly, several of these traits were observed in at least two heterologous expression systems.…”
Section: Main Textmentioning
confidence: 99%